Energy crisis of 2021–2022 as a harbinger of a change in the global energy system - E. A. Rechkina; A. M. Terekhov (Вестник университета)
The energy mode concept, has been characterized. Energy patterns types, history of their formation and development have been summarized. The prerequisites for forming a new energy mode based on the increasing share of renewable energy sources and hydrogen raw materials in the energy production structure have been highlighted. The change of the energy structure will take place in the coming decades. The following scientiﬁc methods of research were used in the paper: literature analysis and analysis of statistical data. Data for the period from 1965 to 2022 were used. The purpose of the study is to identify the role of the energy crisis of 2021–2022 as a factor contributing to a new energy structure formation that will be implemented in the coming decades. The subject of the study is to analyze and evaluate the change of the energy pattern in the international energy market, and the object of the study is the world energy market.